A Novel Analysis Procedure for Estimating Thickness-Independent Horizontal and Vertical Permeabilities from Pressure Data at an Observation Probe Acquired by Packer-Probe Wireline Formation Testers - Onur, M..; Hegeman, P.S.. S.; Gok, I.M.. M.; Kuchuk, F.J.. J. (IPTC, 2009)
Abstract This paper presents a new spherical-flow cubic-analysis procedure for estimating horizontal and vertical permeabilities solely from pressure transient data acquired at an observation probe of the dual-packer-probe wireline formation testers (WFTs) for all inclination angles of the wellbore. The procedure is based on the analytical spherical-flow equation that Onur et al. (2004a) previously presented, and the conventional spherical-flow analysis plot of drawdown or buildup observation probe pressures. This procedure now makes it possible for one to estimate both horizontal and vertical permeabilities from observation- probe pressure data exhibiting spherical flow for packer-probe interval pressure transient tests (IPTTs). The new analysis procedure does not require one to know the formation thickness or to observe the radial flow regime at the dual-packer and/or observation probe. The procedure provides unique estimates of horizontal and vertical permeabilities from observation-probe pressure data obtained along both vertical and horizontal wellbores. However, for slanted well cases, the analysis procedure yields two possible solutions for the horizontal and vertical permeabilities. Therefore, one must use a priori information on permeabilities, from sources such as core data or pretests, to eliminate one of the solutions and identify the appropriate solution for the slanted well cases. For IPTTs that have transitional data from the spherical flow regime to late-radial flow regime, nonlinear regression analysis based on history matching of dual-packer- and/or observation-probe pressure measurements from slanted wells may also help one to estimate correct values of horizontal and vertical permeabilities. We illustrate the applicability of the proposed analysis procedure by considering two synthetic and two field packer-probe IPTT data sets from vertical and slanted wellbores. Introduction Over the last four decades, wireline formation testing has become quite attractive for reservoir pressure profiling, sampling/fluid identification, IPTTs, and in-situ stress testing. IPTTs conducted with packer-probe formation testers provide dynamic permeability and anisotropy information with high vertical resolution along the wellbore (Zimmerman et al. 1990; Pop et al. 1990; Goode and Thambynayagam 1992; Kuchuk et al. 1994). Permeability is one of the most important parameters for both reservoir management and well performance. Permeability and permeability anisotropy, the ratio kv/kh, strongly affect all reservoir displacement processes. Thus, it is becoming increasingly important to determine these values as operators shift their focus from primary to secondary and tertiary recovery. Fig. 1 shows a schematic diagram of a packer-probe interference test (usually referred to as an IPTT) in a deviated well in an anisotropic formation that is bounded vertically and infinite laterally. The schematic represents a general configuration that is valid for all inclination angles (qw) of the wellbore. For instance, if qw = 0o, then we consider an IPTT conducted in a vertical well, whereas if qw = 90o, we consider an IPTT conducted in a horizontal well. In these tests, a dual-packer is set against the formation to serve as a flow source. The pressure transients are measured at both the packer interval and observation probe. Any pressure change at the observation probe due to flow from the packer interval clearly indicates communication within the formation between the two locations. Interpretation of packer and probe data provides one with permeability values in both the vertical and horizontal direction. Furthermore, one can characterize the near-wellbore heterogeneity from IPTTs.